2011
DOI: 10.3727/096368910x539083
|View full text |Cite
|
Sign up to set email alerts
|

Cotransplantation of Mouse Neural Stem Cells (mNSCs) with Adipose Tissue-Derived Mesenchymal Stem Cells Improves mNSC Survival in a Rat Spinal Cord Injury Model

Abstract: The low survival rate of graft stem cells after transplantation into recipient tissue is a major obstacle for successful stem cell therapy. After transplantation into the site of spinal cord injury, the stem cells face not only hypoxia due to low oxygen conditions, but also a lack of nutrients caused by damaged tissues and poor vascular supply. To improve the survival of therapeutic stem cells after grafting into the injured spinal cord, we examined the effects of cotransplanting mouse neural stem cells (mNSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 32 publications
0
41
0
Order By: Relevance
“…This novel strategy can be used to augment the therapeutic efficacy of combined stem cell and gene modulation therapy for SCI. In another study, Oh et al [63] , examined the effects of co-transplanting mouse neural stem cells (mNSCs) and adipose tissue-derived mesenchymal stem cells (ATMSCs) on mNSC viability. It was observed that mNSCs transplanted into rat spinal cords with AT-MSCs showed better survival rates than mNSCs transplanted alone, thereby suggesting that co-transplantation of mNSCs with AT-MSCs is a more effective strategy to improve the survival of transplanted stem cells into the injured spinal cord.…”
Section: Ratmentioning
confidence: 99%
“…This novel strategy can be used to augment the therapeutic efficacy of combined stem cell and gene modulation therapy for SCI. In another study, Oh et al [63] , examined the effects of co-transplanting mouse neural stem cells (mNSCs) and adipose tissue-derived mesenchymal stem cells (ATMSCs) on mNSC viability. It was observed that mNSCs transplanted into rat spinal cords with AT-MSCs showed better survival rates than mNSCs transplanted alone, thereby suggesting that co-transplantation of mNSCs with AT-MSCs is a more effective strategy to improve the survival of transplanted stem cells into the injured spinal cord.…”
Section: Ratmentioning
confidence: 99%
“…This could then protect transplanted and possible host cells from the hypoxia. 7,8,28,29 Several elements, such as the hypoxia-responsive untranslated region, [30][31][32] oxygen-dependant degradation domain sequence, 33,34 RTP801 promoter 35 and Epo enhancer 31,36 have been used to design hypoxia-inducible systems. We have previously confirmed that the Epo enhancer-based system increases gene expression specifically in hypoxic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Guedes and colleagues also examine the possible therapeutic advantage of co-transplantation, acknowledging its beneficial effects towards cell survival. Recent trials show the delivery of neural stem cells combined with adipose-derived stem cells increased neural stem cell survival [2]. Overall, the article skillfully examines the potential of various stem cells, providing valuable background for future discovery.…”
Section: Bone Marrow-derived Stem Cellsmentioning
confidence: 99%